(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to investigate the impact of culture on the quality of financial reporting. The geographical scope of the study includes companies listed on the stock exchanges of Iran, Turkey, Qatar, Bahrain, Iraq, Oman, Saudi Arabia, and the United Arab Emirates, while the timeframe extends from 2015 to 2024. This study is classified as applied research, as the sample comprised 2,029 companies listed on the aforementioned stock exchanges. The results indicate that coherence is positively and significantly correlated with the quality of financial reporting, while authoritarianism and dominance are negatively and significantly correlated. Hierarchy, however, does not show a significant correlation with the quality of financial reporting. In general, culture influences multiple aspects of accounting; the higher the level of social justice, peace, and security, the higher the quality of financial reporting. It is worth noting that accounting is one of the most important tools for determining the optimal allocation of resources to maximize returns, according to signal theory. Optimal resource allocation can provide social security and ensure the sustainability of optimal production. Since dominance and authoritarianism prioritize self-interest, this is reflected in accounting through agency and self-interest theories. When private interests overshadow collective interests, abuse and fraudulent reporting become more prevalent. Therefore, the dominance of a self-interest culture in society can similarly influence accounting practices, leading to a decline in the quality of financial reporting.